Factors Associated with the Joint Physical Custody of European Children - Salin, Milla; Meyer; Daniel R.; Hakovirta; Mia; Lindroos, Eija (Springer Dordrecht, 2025)
Understanding patterns of children’s living arrangements (physical custody) in separated families and the factors related to joint physical custody are crucial as custody patterns have significant implications for the well-being of children and parents. In this study we use the 2021 European Union Statistics on Income and Living Conditions Survey (EU-SILC) to provide new evidence of children’s post-separation living arrangements in Europe. Our sample (n = 7,461) is restricted to children of separated or divorced parents residing in their mother’s household and having another parent residing outside of the household. We analyze both the individual-level socioeconomic, family-and child-related characteristics, and country-level variables to explain variation in children’s joint physical custody arrangements. We find that joint physical custody is higher among boys and children in the age groups 6–10 and 11–15. We also find that children with more socioeconomically advantaged mothers (higher education, employed, higher income, homeowners) are more likely to have joint physical custody. Importantly, controlling for individual-level characteristics, both the legal and the gender equality context shape the prevalence of joint physical custody, suggesting that country-level policies and norms may be important.